Comparative Analysis of Endophytic Curtobacterium Species Reveals Commonalities and Adaptations - Annabel Arhin; Sydney Wiegand; Isabella Foriska; Kiersten Brown; Kylee Crayne; Kaitlyn Stroscio; Rajinikanth Mohan (Bacteria, 2025)
Curtobacterium species are increasingly recognized as plant pathogens and soil decomposers, but their prevalence and function as plant endophytes in aerial organs are less clear. In this study, we isolated six endophytic Curtobacterium species from the fruits, flower petals (previously unreported) and stem tissue of plants from diverse environments and examined their general characteristics. We found that all Curtobacterium endophytes belonging to three major Curtobacterium clusters—C. oceanosedimentum (a group not previously recognized as endophytic), C. luteum and C. flaccumfaciens—shared some common features. All or nearly all isolates tested were pigmented, displayed moderate salt tolerance and, surprisingly, were psychrotolerant, being able to grow at 6 °C. The exception was a fruit C. luteum isolate that appears to have evolved thermotolerance (up to 45 °C) instead as a likely adaptation to its environment. All isolates were able to metabolize starch and casein and solubilize inorganic phosphate, indicating conserved secreted hydrolase activity, but only isolates in the C. oceanosedimentum group were able to absorb and metabolize citrate. Finally, all endophytes tested were able to ferment the plant sugars sucrose and fructose, while they differed in their ability to use other sugars. Thus, this study documents common traits and adaptations in various Curtobacterium endophytes, and the presence of these isolates in floral and fruit organs implies the possible seed-borne inheritance of these isolates.